Towards programmable on‐demand lightpath services: current state‐of‐the‐art and open research areas. Issue 6 (1st November 2019) - Nkosi, Mpho C.; Mamushiane, Lusani; Lysko, Albert A.; Johnson, David L.; Engelbrecht, Andries P.
Abstract : With emerging programmable network architectures gaining momentum in the networking industry, it is necessary to look at how the services currently offered on traditional network architectures can be fully migrated to the programmable networks. In traditional networks, lightpaths are used for providing high‐bandwidth consuming services that are usually sensitive to delay. Lightpath scheduling requires admission control mechanisms, routing and wavelength assignment algorithms, and protection and restoration mechanisms that ensure reliable and efficient lightpath routing. Software defined networking (SDN) is the emerging programmable network architecture that paves the way for easier network management and configuration by using application programming interfaces. The state‐of‐the‐art in lightpath routing for wavelength division multiplexing networks focusing on lightpath scheduling, routing, protection and restoration in optical software defined networks is surveyed. Moreover, open research issues for SDN lightpath routing solution are discussed.